DIPLOMASI INDONESIA DALAM MEMASUKAN CPO PADA ENVIRONMENTAL GOODS LIST DI APEC PADA TAHUN 2012-2017 - Maria Anastasia Siagian (Journal of Diplomacy and International Studies, 2019)
Indonesia, being the top global CPO producer, makes CPO as one of their national interest due to the great contribution of CPO to Indonesia’s economics as well as to their citizens. This brings Indonesia to utilize regional forums, viz. Asia-Pacific Economic Cooperation (APEC), in order to build Indonesia’s CPO image and also to gain from tariff reductionto 5% or less through the Environmental Goods (EGs) intiative in 2012. Lack of success in Indonesia’s diplomacy in the EGs initiative have failed its goal to have CPO included in the EGs list. Hence, in 2013 Indonesia managed to shift its strategy by initiating the Development Products which also have CPO included in the products list Indonesia proposed. Up until 2017, no decisions and deals were made among the APEC countries regarding Indonesia’s Development Products initiative. This research aims to analyze the negotiations process which Indonesia had done through EGs to Development Products using the qualitative research approach. This research finds that the result of this negotiation is the result of the power structure between Indonesia and their opponents during the negotiation of both EGs and Development Products.